Importance of the “Teniente Coronel Luis A. Mantilla” airport for the tourist development of Tulcán - Pillajo Borja, Hernán Patricio (Tierra Infinita, 2021)
In this investigation, the conditions in which the “Teniente Coronel Luis A Mantilla” airport of the city of Tulcán are identified, with a second category according to the AIP (Aeronautical Information Publication), currently closed for commercial use and the repercussions that may have for the development of tourism in said city. Through the descriptive observation, it can be established that this air infrastructure meets most operating parameters established by the Regulation of the General Directorate of Civil Aviation to provide the air transport service for both domestic and foreign passengers. The airports promote the specialization of a part of the local population in activities related to the operation of this, generating labor opportunities in the construction process and, later, in the operation thereof. For this reason,  they are an important part of the tourism development of a sector and, as such, the population of Tulcán assumes that 85% consider that the airport will improve the entrance to national and foreign tourism.
Keywords: Airport; Tulcan; tourism; tourist infrastructure